2017
DOI: 10.3892/etm.2017.4617
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of glycyrrhizin on myocardial ischemia/reperfusion injury-induced oxidative stress, inducible nitric oxide synthase and inflammatory reactions through high-mobility group box 1 and mitogen-activated protein kinase expression

Abstract: Abstract. Glycyrrhizin, which is a type of perennial leguminous caudex, has been used in various Asian countries, including P.R. China, India and Japan, for thousands of years. The present study was designed to investigate the protective effect of glycyrrhizin on myocardial ischemia/reperfusion (I/R) injury through oxidative stress, inducible nitric oxide synthase (iNOS), and inflammatory reactions via high-mobility group box 1 (HMGB1) and mitogen-activated protein kinase (MAPK) expression. Sprague-Dawley rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Glycyrrhizin (GL) is a natural inhibitor of extracellular HMGB-1 and inhibits the formation of pro-inflammatory cytokines ( 77 , 78 ). In a rat model of MI, the use of GL dose- dependently attenuated IRI ( 78 ).…”
Section: Damage-associated Molecular Patterns Related To Myocardial Imentioning
confidence: 99%
See 1 more Smart Citation
“…Glycyrrhizin (GL) is a natural inhibitor of extracellular HMGB-1 and inhibits the formation of pro-inflammatory cytokines ( 77 , 78 ). In a rat model of MI, the use of GL dose- dependently attenuated IRI ( 78 ).…”
Section: Damage-associated Molecular Patterns Related To Myocardial Imentioning
confidence: 99%
“…Glycyrrhizin (GL) is a natural inhibitor of extracellular HMGB-1 and inhibits the formation of pro-inflammatory cytokines ( 77 , 78 ). In a rat model of MI, the use of GL dose- dependently attenuated IRI ( 78 ). When added to the preservation solution during cold storage in a HTx mouse model, GL improved cardiac allograft function and resulted in less myocardial damage ( 79 ).…”
Section: Damage-associated Molecular Patterns Related To Myocardial Imentioning
confidence: 99%
“…Therefore, we will investigate the therapeutic effect of GB on allergic asthma in further study. In addition, we will explore the antioxidant effects of GB because its three components have antioxidant effects [ 36 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is clinically used as an antiulcer, antiallergic, antioxidant, antiviral and anticancer agent (6), several studies have also demonstrated its potential protective effects against I/R-and H/R-induced endothelial injury (6,7). Cai et al (8), reported that GA elicits protective effects against myocardial I/R injury by regulating oxidative stress and inflammatory reactions via the transcriptional modification of high-mobility group box 1 and mitogen-activated protein kinase in rats (8). However, whether GA exhibits protective effects against I/R-and H/R-induced injury in coronary artery endothelial cells (CAECs) is not completely understood.…”
Section: Introductionmentioning
confidence: 99%